Danger of Herbal Tea: A Case of Acute Cholestatic Hepatitis Due to Artemisia annua Tea - Ruperti-Repilado, Francisco Javier; Haefliger, Simon; Rehm, Sophia; Zweier, Markus; Rentsch, Katharina M.; Blum, Johannes; Jetter, Alexander; Heim, Markus; Leuppi-Taegtmeyer, Anne; Terracciano, Luigi; Bernsmeier, Christine (Frontiers in Medicine, 2019)
Background:Artemisia annua is a Chinese medicinal herb. Artemisinin-derivatives are recommended as part of a combination treatment for uncomplicated malaria. Herbal and dietary supplements (HDS) are increasingly used worldwide and HDS-induced liver injury is becoming a growing concern. Case Report: We present the first case of severe acute cholestatic hepatitis due to the intake of Artemisia annua tea as chemoprophylaxis for malaria in a patient returning from Ethiopia. The patients presented with jaundice, elevated transaminases, and parameters of cholestasis (total bilirubin 186.6 μmol/L, conjugated bilirubin 168.5 μmol/L). A liver biopsy showed a portal hepatitis with lymphocytic infiltration of the bile ducts and diffuse intra-canalicular and intra-cytoplasmic bilirubinostasis. The toxicologic analysis of the Artemisia tea revealed the ingredients arteannuin b, deoxyartemisin, campher, and scopoletin. There were no other identifiable etiologies of liver disease. The Roussel Uclaf Causality Assessment Method (RUCAM) score assessed a “probably” causal relationship. Sequencing of genes encoding for hepatic transporters for bile acid homeostasis (BSEP, MDR3, and FIC1) found no genetic variants typically associated with hereditary cholestasis syndromes. Normalization of bilirubin occurred 3 months after the onset of disease. Conclusion: The use of artemisinin-derivatives for malaria prevention is ineffective and potentially harmful and should thus be discouraged. Moreover, the case demonstrates our as yet inadequate understanding of the pathophysiology and susceptibility to HDS induced liver injury.